2012
DOI: 10.5812/ijhrba.4624
|View full text |Cite
|
Sign up to set email alerts
|

Trauma, Dissociation,and High-Risk Behaviors

Abstract: Implementing effective strategies to prevent high risk behaviors among at risk populations. Epidemiological studies and clinical findings have shown an association between trauma and dissociation; dissociative experiences are also more prevalent among select populations such as substance dependent individuals and criminal offenders. In the present non-systematic review, we explored the association between trauma, dissociation, and high-risk behaviors. We aimed to find if the presence of dissociative symptoms c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Lyssenko et al (2018) suggested that the experience of dissociation can induce stress itself because it not only disrupts neurocognitive functioning but can also be perceived as losing control [31]. Kianpoor and Bakhshani (2012) reported that dissociation related with high-risk behaviors such as violence, heavy drinking, the use of illicit drugs, and dangerous driving [62]. From a clinical perspective, this finding underlines the importance of careful evaluation of dissociation symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Lyssenko et al (2018) suggested that the experience of dissociation can induce stress itself because it not only disrupts neurocognitive functioning but can also be perceived as losing control [31]. Kianpoor and Bakhshani (2012) reported that dissociation related with high-risk behaviors such as violence, heavy drinking, the use of illicit drugs, and dangerous driving [62]. From a clinical perspective, this finding underlines the importance of careful evaluation of dissociation symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…It can be a single or a continuing event that threatens an individual and/or his or her family's safety and survival. Traumatic events include (1) abuse; (2) exposure to violence; (3) natural disaster; (4) war; (5) abandonment; (6) personal attack by another person or animal; (7) witnessing catastrophic accidents or violence to others; (8) becoming a victim of 290 O. D. TAYLOR kidnapping, rape, or torture; and (9) experiencing a medical procedure, accident, or serious illness (Moroz, 2005;Kianpoor & Bakhshani, 2012).…”
Section: Adolescent Trauma and Substance Usementioning
confidence: 99%
“…Contemporary youth are beset with an onslaught of distressing life events that threaten to compromise their mental health. Behavioral health data suggest mental health and substance abuse disorders often coexist (NIDA, 2012); therefore, adolescents experiencing trauma are at risk for developing a substance use disorder (SUD) and other types of disorders (i.e., dissociative disorder, borderline personality disorder, self-mutilation, violence; Kianpoor & Bakhshani, 2012) if their mental health issues are not addressed. Researchers discovered that youth who have been exposed to trauma are highly likely to develop anxiety disorders and to show a pattern of increased risky sexual behaviors.…”
Section: Adolescent Trauma and Substance Usementioning
confidence: 99%
“…Based on Timko et al ( 10 ) research, violence and abuse survivors are often involved in various coping behaviors; SA is also a way of overcoming negative psychological effects of past experiences. Because, trauma affects many levels of functioning aspects such as somatic, emotional, cognitive, behavioral, and characterlogical ( 11 ); those who experienced severe anxiety and depression states may be more vulnerable to alcohol and SA.…”
Section: Backgroundsmentioning
confidence: 99%